316 Ovarian tumor in patients with previous gastrointestinal carcinoma. (18th September 2019) - Nobrega, F; Anton, C; Lopes de Farias e Silva, A; Nogueira Dias Genta, ML; Mancusi de Carvalho, JP; Paula Carvalho, J
Abstract : Objectives: To evaluate demographic and clinical-pathological characteristics of ovarian tumors diagnosed in women with previous gastrointestinal cancers. Methods: A tranversal study of 59 patients with diagnosis of ovarian tumors who had previously been treated for gastrointestinal adenocarcinoma at a hospital in Sao Paulo, Brazil, from 2009 to 2018. Demographic data were collected: age, follow-up of primary gastrointestinal tumor, tumor markers CA-125, CA- 19.9 and CEA, radiological characteristics, type and extent of surgery performed, amount of residual disease, primary tumor site, anatomopathological diagnosis and survival. Results: The primary gastrointestinal carcinoma sites were: stomach (15.3%), colorectal (64.4%), appendix (3.4%), pancreas (3.4%), gallbladder (3.4%) and undetermined gastrointestinal cancer (10.2%). The median follow-up was 16 (1–87) months. The overall survival from the diagnosis of gastrointestinal carcinoma was 33 (2–187) months and the overall survival from ovarian tumor diagnosis was 16 (1–87) months. The mortality rate varied according to the site of origin of gastrointestinal carcinoma: stomach (77.8%), colorectal (53.1%), appendix (50%), gallbladder (50%), pancreas (50%) and undetermined gastrointestinal carcinoma (16.7%). Conclusions: Metastatic gastrointestinal tumors to the ovaries present variable overall survival according to the primary site of origin. Tumors of the stomach, gallbladder and pancreas present worse prognosis. Colorectal metastatic tumors are the most frequent and the ones with the highest overall survival. These differences should be considered when deciding whether to perform surgical treatment in these patients with metastatic tumors.